PERAN LITERASI POLITK GENERASI MUDA DALAM MENGUATKAN NILAI NILAI DEMOKRASI DI ERA DIGITAL (STUDI PADA MAHASISWA PPKn UNIVERSITAS MUHAMMADIYAH MAKASSAR) - Fausia, St Nur Nabila; Nur, Jumiati; Syahrir, Musdalifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is based on the importance of the strategic role of the young generation in maintaining the sustainability of democracy in the midst of the challenges of the digital era. Although PPKn students are prepared academically to understand the values of democracy, a phenomenon is found where students still face obstacles in deliberation due to limited political literacy. This research aims to describe the level of political literacy, the role of students, as well as supporting and inhibiting factors in strengthening democracy inthe digital era. The research method used is qualitative descriptive. Data collection was carried out through interviews with informants of the 2024 class of 2024 students, observations, and documentation. Data analysis is carried out critically by linking field findings to the theory of political literacy and democratic values. The research results show that political literacy plays a significant role as a shield against digital disinformation through information verification (fact check) before spreading it. The role of students is manifested in the internalization of civic virtue, such as the use of the raise hand feature and the polite presentation of arguments in virtual spaces (such as Google Meet). The main supporting factors include an academic environment that encourages open discussion and digital media access to actual issues. Meanwhile, inhibiting factors include the existence of political apathy due to a negative perception of national political practices as well as the risk of polarization on social media. This research concludes that strengthening political literacy not only improves the quality of academic participation, but also forms a healthy participatory political culture in the digital era.